2022
DOI: 10.3390/ijerph19127210
|View full text |Cite
|
Sign up to set email alerts
|

Urban Inundation under Different Rainstorm Scenarios in Lin’an City, China

Abstract: Under the circumstances of global warming and rapid urbanization, damage caused by urban inundation are becoming increasingly severe, attracting the attention of both researchers and governors. The accurate simulation of urban inundation is essential for the prevention of inundation hazards. In this study, a 1D pipe network and a 2D urban inundation coupling model constructed by InfoWorks ICM was used to simulate the inundation conditions in the typical urbanized area in the north of Lin’an. Two historical rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 43 publications
0
3
0
1
Order By: Relevance
“…It is confirmed that both drainage network density and elevation are important factors for the probability of urban flood inundation. On a small scale, such as a 1 km resolution, topography and drainage mainly determine the inundation level (Chen et al 2022). Because Jingdezhen City is located along the Changjiang River, fluvial floods also affect urban inundation.…”
Section: Discussionmentioning
confidence: 99%
“…It is confirmed that both drainage network density and elevation are important factors for the probability of urban flood inundation. On a small scale, such as a 1 km resolution, topography and drainage mainly determine the inundation level (Chen et al 2022). Because Jingdezhen City is located along the Changjiang River, fluvial floods also affect urban inundation.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the fullprocess simulation of urban floods, the 2D model does not account for the influence of underground drainage pipes, which is a limitation. Therefore, to enhance the accuracy of coastal city flood simulations, many researchers have focused on the coupling of 1D drainage network models with 2D surface flow models [96][97][98][99]. By establishing a fluid exchange between the 2D and 1D models, a more comprehensive urban flood model can be constructed.…”
Section: Isolated Scenario Analysis (Isa)mentioning
confidence: 99%
“…2D hydrodynamic modeling is often used to simulate the evolution of the vertical and horizontal flow velocity distribution in areas such as urban surfaces, rivers, and lakes. Mainstream simulation software for urban flood and waterlogging disasters includes SWMM (Koc et al, 2021; Paule‐Mercado et al, 2017; Rai et al, 2018; Sun et al, 2022; Y. Yang et al, 2021; Zeng et al, 2021), HEC‐RAS (Bush et al, 2022; Shustikova et al, 2019; Tamiru & Wagari, 2022; Vozinaki et al, 2017), LISFLOOD‐FP (Z. Liu & Merwade, 2018; Wilson et al, 2007; X. Wu, Wang, et al, 2018), InfoWorks ICM (Chen et al, 2022; Hosseinzadehtalaei et al, 2021; Peng et al, 2016; Z. Zhu et al, 2016), MIKE (Bisht et al, 2016; C. Q. Li & Wang, 2012; H. L. Liu et al, 2007; M. M. Rahman et al, 2011), and FLO‐2D (Erena et al, 2018; Hsu et al, 2010; M. H. Li et al, 2011). In addition, variations in the flow fields of some key areas, including estuaries, coasts, water pumps, and sluices, are also simulated with 3D hydrodynamic modeling, while the anisotropy of fluids is fully considered.…”
Section: A Coordinated Drainage and Regulation Modelmentioning
confidence: 99%
“…Liu & Merwade, 2018;Wilson et al, 2007;X. Wu, Wang, et al, 2018), InfoWorks ICM (Chen et al, 2022;Hosseinzadehtalaei et al, 2021;Peng et al, 2016;Z. Zhu et al, 2016), MIKE (Bisht et al, 2016;C.…”
Section: Prediction and Forecast Systems For Urban Flood And Waterlog...unclassified